Analysis of Structural Changes in Andalusian Economy Using Social Accounting Matrices - Pilar Campoy Mu\~noz; Manuel Alejandro Cardenete Flores; María del Carmen Delgado López (Austrian Institute of Economic Research (WIFO), 2014)
The goal of this work is to analyse the possible effects of the crisis on Andalusian economic structure during the period 2005-2010 using Social Accounting Matrices (SAMs). SAMs describe the circular flow of income and provide a statistical database for the analysis of the key sectors in the regional economy, the linkages between these sectors and their relevance in terms of employment. Specifically, a linear SAM model is applied to calculate the decomposition of multipliers in their three effects (direct, indirect and induced), as well as the multipliers of employment for each sector in the regional economy. The comparative analysis of the different years allows drawing some conclusions about the changes in the productive structure as a consequence of the crisis.
Keywords: 330; Regional Accounts; Input- Output Tables; Social Accounting Matrices; Multisectoral Models; Key Sectors